The indirect effect of sleep quality on stress-related psychosocial outcomes in adolescents: an investigation across genders - Koike, Camila; Nestor, Bridget A.; Baumer, Andreas M.; Kossowsky, Joe (Frontiers in Psychology, 2025)
BackgroundSleep is foundational for adolescent psychosocial outcomes though often compromised by normative developmental changes and external factors.MethodsThis cross-sectional study examined sleep quality as a mechanism linking stress and psychosocial outcomes and explored gender differences.ResultsAdolescents (N = 236; Mean = 15.66; SD = 1.07, 46.19% female) completed self-report measures assessing sleep quality and psychosocial outcomes. Structural equation modeling was used to test the potential mediating effect of sleep quality on associations between stress and psychosocial outcomes. Results indicated sleep quality accounted for 82.0% of the total effect of stress on school functioning (β = −0.45, p < 0.001) and 61.9% of the total effect of stress on pain (β = 0.14, p < 0.001). A larger indirect effect of sleep quality on school functioning (βdiff = −0.27, p = 0.006) emerged for boys than girls, and the effect of sleep quality on pain was significant only for girls (β = 0.20, p = 0.003, 65.0% of total effect).ConclusionSleep quality explained a large proportion of the cross-sectional association between stress and school functioning and pain. Sleep quality represents a modifiable transdiagnostic pathway that may buffer the effects of stress in adolescence.